Cutting Tools

Cutting tools with MOC 1-x or TAC 1-y coatings on a substrate provide enhanced durability and abrasion resistance, addressing the need for longer tool life in high-speed and high-efficiency processing.

JP7622344B2Active Publication Date: 2025-01-28SUMITOMO ELECTRIC HARDMETAL CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023103471
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-05-20
Filing Date
2023-06-23
Publication Date
2025-01-28
Estimated Expiration
2042-02-09

AI Technical Summary

Technical Problem

The demand for cutting tools with improved durability and abrasion resistance is increasing due to the need for high-speed and high-efficiency processing, as existing tools often fail to maintain tool life under such conditions.

Method used

The cutting tools are designed with a substrate coated by a film comprising MOC 1-x or TAC 1-y layers, where MOC and TAC have specific crystal structures and compositions, and are applied using the Arc Ion Plating method to enhance durability and abrasion resistance.

Benefits of technology

The cutting tools exhibit extended tool life and improved wear resistance, making them suitable for high-speed and high-efficiency processing applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007622344000005
    Figure 0007622344000005
  • Figure 0007622344000006
    Figure 0007622344000006
  • Figure 0007622344000007
    Figure 0007622344000007
Patent Text Reader

Abstract

To provide a cutting tool that has a long tool life even in high-speed, high-efficiency processing.SOLUTION: A cutting tool includes a base material and a coating arranged on the base material. The coating includes a first layer and a hard coating layer arranged between the base material and the first layer. The first layer is composed of a TaC1-y layer made of a chemical compound shown by TaC1-y, and the chemical compound shown by TaC1-y includes a hexagonal crystal structure in an amount of 95 mass% or more, the y being 0.40-0.60. The hard coating layer includes a first unit layer, and a composition of the first unit layer is different from a composition of the first layer. The first unit layer is formed of a chemical compound composed of at least one kind of element selected from the group consisting of a group 4 element, a group 5 element, and a group 6 element in a periodic table, aluminum and silicon, or at least one kind of element selected from the group consisting of a group 4 element, a group 5 element, and a group 6 element in the periodic table, aluminum and silicon and at least one kind of element selected from the group consisting of carbon, nitrogen, oxygen and boron.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a cutting tool. This application claims priority to international applications PCT / JP2021 / 019172 filed on May 20, 2021 and PCT / JP2021 / 019173 filed on May 20, 2021. All contents of the international applications are incorporated herein by reference. [Background technology]

[0002] Conventionally, various studies have been conducted with the aim of extending the life of cutting tools. For example, Patent Document 1 discloses a method for forming a WC 1-x A cutting tool having disposed thereon a coating including a layer is disclosed. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2019 / 181742 Summary of the Invention

[0004] A cutting tool according to the present disclosure includes a substrate and a coating disposed on the substrate, The coating comprises a first layer, The first layer is MoC 1-x MoC consisting of the compound represented by 1-x layer or TaC 1-y TaC consisting of the compound represented by 1-y It consists of layers, Said MoC 1-x The compound represented by the formula (I) has a hexagonal crystal structure, The x is equal to or greater than 0.40 and equal to or less than 0.60, The TaC 1-y The compound represented by the formula (I) contains 95% by mass or more of a hexagonal crystal structure, The cutting tool, wherein y is equal to or greater than 0.40 and equal to or less than 0.60. [Brief description of the drawings]

[0005] [Figure 1] FIG. 1 is a perspective view illustrating one embodiment of a cutting tool. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a cutting tool according to one aspect of this embodiment. [Diagram 3] FIG. 3 is a schematic cross-sectional view of a cutting tool according to another aspect of the present embodiment. [Figure 4] FIG. 4 is a schematic cross-sectional view of a cutting tool according to another aspect of the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0006] [Problem that this disclosure aims to solve] In recent years, there has been an increasing demand for high-speed, high-efficiency machining under heavy loads, and cutting tools capable of high speed and high efficiency and having a long tool life are in demand.

[0007] [Effects of this disclosure] According to the present disclosure, it is possible to provide a cutting tool having a long tool life even in high-speed, high-efficiency machining.

[0008] [Description of the embodiments of the present disclosure] First, the embodiments of the present disclosure will be listed and described. (1) A cutting tool according to the present disclosure is a cutting tool including a substrate and a coating disposed on the substrate, The coating comprises a first layer, The first layer is MoC 1-x MoC consisting of the compound represented by 1-x layer or TaC 1-y TaC consisting of the compound represented by 1-y It consists of layers, Said MoC 1-x The compound represented by the formula (I) has a hexagonal crystal structure, The x is equal to or greater than 0.40 and equal to or less than 0.60, The TaC 1-y The compound represented by the formula (I) contains 95% by mass or more of a hexagonal crystal structure, The cutting tool, wherein y is equal to or greater than 0.40 and equal to or less than 0.60.

[0009] According to the present disclosure, it is possible to provide a cutting tool having a long tool life even in high-speed, high-efficiency machining.

[0010] (2) It is preferable that the first layer does not contain free carbon, which improves the chipping resistance and wear resistance of the cutting tool.

[0011] (3) The hardness of the first layer is 2700 mgf / μm 2 More than 4200mgf / μm 2 It is preferable that the cutting tool has the following properties: This improves the chipping resistance and wear resistance of the cutting tool.

[0012] (4) It is preferable that the first layer is in contact with the base material, whereby the cutting tool can have excellent chipping resistance and wear resistance.

[0013] (5) The coating further includes a hard coating layer disposed between the substrate and the first layer, The hard coating layer includes a first unit layer, The composition of the first unit layer is different from the composition of the first layer, The first unit layer preferably comprises at least one element selected from the group consisting of Group 4, 5, and 6 elements of the periodic table, aluminum, and silicon, or comprises a compound comprising at least one element selected from the group consisting of Group 4, 5, and 6 elements of the periodic table, aluminum, and silicon, and at least one element selected from the group consisting of carbon, nitrogen, oxygen, and boron.

[0014] This improves the chipping resistance and wear resistance of the cutting tool.

[0015] (6) The hard coating layer is composed of the first unit layer, The thickness of the first unit layer is preferably 0.1 μm or more and 15 μm or less.

[0016] This improves the chipping resistance and wear resistance of the cutting tool.

[0017] (7) The hard coating layer further includes a second unit layer, the composition of the second unit layer is different from the composition of the first layer and the composition of the first unit layer, the second unit layer is made of at least one element selected from the group consisting of Group 4 elements, Group 5 elements, Group 6 elements, aluminum, and silicon, or made of a compound containing at least one element selected from the group consisting of Group 4 elements, Group 5 elements, Group 6 elements, aluminum, and silicon, and at least one element selected from the group consisting of carbon, nitrogen, oxygen, and boron, It is preferable that the first unit layers and the second unit layers are each alternately laminated one or more times to form a multilayer structure.

[0018] This improves the chipping resistance and wear resistance of the cutting tool.

[0019] (8) The thickness of the first unit layer is 1 nm or more and 100 nm or less, The second unit layer preferably has a thickness of 1 nm to 100 nm, which improves the chipping resistance and wear resistance of the cutting tool.

[0020] (9) The thickness of the first layer is 0.1 μm or more and 10 μm or less, The thickness of the hard coating layer is preferably 0.1 μm or more and 10 μm or less, which improves the chipping resistance and wear resistance of the cutting tool.

[0021] (10) The thickness of the coating is preferably 0.2 μm or more and 20 μm or less, which improves the chipping resistance and wear resistance of the cutting tool.

[0022] (11) The substrate preferably contains at least one material selected from the group consisting of cemented carbide, cermet, high speed steel, ceramics, cubic boron nitride sintered body, and diamond sintered body, thereby enabling the cutting tool to have excellent hardness and strength even at high temperatures.

[0023] [Details of the embodiment of the present disclosure] Specific examples of the cutting tool of the present disclosure will be described below with reference to the drawings. In the drawings of the present disclosure, the same reference numerals represent the same or corresponding parts. Furthermore, dimensional relationships such as length, width, thickness, and depth have been appropriately changed for clarity and simplification of the drawings, and do not necessarily represent actual dimensional relationships.

[0024] In this specification, the expression "A to B" means the upper and lower limits of a range (i.e., A or more and B or less). When no unit is specified for A and a unit is specified only for B, the unit of A and the unit of B are the same.

[0025] In this specification, when a compound is expressed by a chemical formula, unless the atomic ratio is particularly limited, it is intended to include any conventionally known atomic ratio and is not necessarily limited to the stoichiometric range. For example, when "TiAlN" is written, the ratio of the numbers of atoms constituting TiAlN includes any conventionally known atomic ratio.

[0026] [Embodiment 1: Cutting tool] A cutting tool according to the present disclosure (hereinafter also referred to as embodiment 1 or this embodiment) is a cutting tool including a substrate and a coating disposed on the substrate, The coating comprises a first layer, The first layer is MoC 1-x MoC consisting of the compound represented by 1-x layer or TaC 1-y TaC consisting of the compound represented by 1-y It consists of layers, Said MoC 1-x The compound represented by the formula (I) has a hexagonal crystal structure, The x is equal to or greater than 0.40 and equal to or less than 0.60, The TaC 1-y The compound represented by the formula (I) contains 95% by mass or more of a hexagonal crystal structure, The cutting tool, wherein y is equal to or greater than 0.40 and equal to or less than 0.60.

[0027] The cutting tool of this embodiment (hereinafter, sometimes simply referred to as "cutting tool") includes a substrate and a coating disposed on the substrate. The cutting tool may be, for example, a drill, an end mill, an indexable cutting tip for a drill, an indexable cutting tip for an end mill, an indexable cutting tip for a milling cutter, an indexable cutting tip for a turning cutter, a metal saw, a gear cutting tool, a reamer, a tap, or the like.

[0028] FIG. 1 is a perspective view illustrating one embodiment of a cutting tool. A cutting tool having such a shape is used, for example, as an indexable cutting tip. The cutting tool 10 has a rake face 1, a flank face 2, and a cutting edge ridge 3 where the rake face 1 and the flank face 2 intersect. That is, the rake face 1 and the flank face 2 are surfaces that are connected to each other with the cutting edge ridge 3 in between. The cutting edge ridge 3 constitutes the cutting edge tip of the cutting tool 10. The shape of such a cutting tool 10 can also be understood as the shape of the base material of the cutting tool. That is, the base material has a rake face, a flank face, and a cutting edge ridge that connects the rake face and the flank face.

[0029] <Base material> The substrate of this embodiment can be any substrate known in the art. For example, the substrate preferably includes at least one selected from the group consisting of cemented carbide (for example, tungsten carbide (WC)-based cemented carbide, WC-Co-based cemented carbide, WC-TaC-Co-based cemented carbide, cemented carbide with carbonitrides such as Cr, Ti, Ta, Nb, etc.), cermet (mainly composed of TiC, TiN, TiCN, etc.), high-speed steel, ceramics (titanium carbide, silicon carbide, silicon nitride, aluminum nitride, aluminum oxide, etc.), cubic boron nitride sintered body (cBN sintered body) and diamond sintered body, and more preferably includes at least one selected from the group consisting of cemented carbide, cermet and cBN sintered body.

[0030] In addition, when a cemented carbide is used as the substrate, the effect of this embodiment is exhibited even if such a cemented carbide contains free carbon or an abnormal phase called an η phase in the structure. The substrate used in this embodiment may have a modified surface. For example, in the case of a cemented carbide, a de-β layer may be formed on the surface, and in the case of a cermet, a surface hardened layer may be formed. Even if the surface is modified in this way, the effect of this embodiment is exhibited.

[0031] When the cutting tool is an indexable cutting tip (such as an indexable cutting tip for milling), the substrate may or may not have a chip breaker. The shape of the ridge of the cutting edge may be any of the following: sharp edge (the ridge where the rake face and the flank intersect), honing (shape in which a radius is added to the sharp edge), negative land (chamfered shape), and a combination of honing and negative land.

[0032] <Coating> The "coating" according to this embodiment has the effect of improving various characteristics of the cutting tool, such as chipping resistance and wear resistance, by covering at least a part of the surface of the substrate. Here, "at least a part of the surface of the substrate" includes a part that comes into contact with the workpiece during cutting. The part that comes into contact with the workpiece can be, for example, a region on the surface of the substrate that is within 2 mm from the cutting edge. Note that even if a part of the substrate is not covered with the coating or the configuration of the coating is partially different, this does not deviate from the scope of this embodiment.

[0033] As shown in Fig. 2, the coating 4 can be composed of a first layer 12. As shown in Fig. 3 and Fig. 4, the coating 4 can include the first layer 12 and a hard coating layer 13 disposed between the first layer 12 and a substrate 11. The coating 4 can include other layers in addition to the first layer 12. Examples of the other layers include an underlayer (not shown) disposed between the hard coating layer and the substrate, an intermediate layer (not shown) disposed between the first layer and the hard coating layer, and a surface layer (not shown) disposed on the first layer.

[0034] The thickness of the coating is preferably 0.1 μm to 20 μm, more preferably 0.1 μm to 10 μm, more preferably 0.2 μm to 20 μm, more preferably 0.2 μm to 10 μm, more preferably 0.3 μm to 10 μm, even more preferably 0.5 μm to 10 μm, even more preferably 1 μm to 6 μm, and particularly preferably 1.5 μm to 4 μm. When the thickness is 0.1 μm or more, the wear resistance of the cutting tool is improved. When the thickness is 0.2 μm or more, the wear resistance of the cutting tool is further improved. When the thickness is 20 μm or less, peeling or destruction of the coating when a large stress is applied between the coating and the substrate during interrupted processing is easily suppressed. Here, the thickness of the coating is MoC 1-x layer, TaC 1-yThe thickness of the coating refers to the sum of the thicknesses of the layers constituting the coating, such as the MoC layer, the hard coating layer, and the undercoat layer. The thickness of the coating is determined by measuring three arbitrary points on a cross-sectional sample parallel to the normal direction of the surface of the substrate using a transmission electron microscope (TEM) and averaging the thicknesses of the three measured points. 1-x layer, TaC 1-y The same applies to the case where the thickness of each of the layer, the hard coating layer (the first unit layer, the second unit layer) and the underlayer is measured. As a transmission electron microscope, for example, a spherical aberration corrector, JEM-2100F (trademark) manufactured by JEOL Ltd., can be mentioned.

[0035] Furthermore, as long as measurements are performed on the same sample, there is almost no variation in the measurement results even if the measurement area is selected in different locations and performed multiple times, and it has been confirmed that setting the measurement area arbitrarily is not arbitrary.

[0036] <First layer> In this embodiment, the coating includes a first layer, the first layer being MoC 1-x MoC consisting of the compound represented by 1-x layer or TaC 1-y TaC consisting of the compound represented by 1-y It consists of layers.

[0037] <MoC 1-x Layer> In this embodiment, MoC 1-x The layer is MoC 1-x It consists of a compound represented by the formula "MoC 1-x (hereinafter, "MoC 1-x ") means molybdenum carbide in which the atomic ratio of carbon (C) is 1-x when the atomic ratio of molybdenum element (Mo) is 1. The above MoC 1-x The layer may contain unavoidable impurities as long as the effects of the cutting tool according to the present embodiment are not impaired. Examples of the unavoidable impurities include hydrogen, oxygen, nitrogen, and argon. The content ratio of the unavoidable impurities is as follows: MoC 1-xThe content of the impurity is preferably 0% by mass or more and 0.2% by mass or less with respect to the total mass of the layer. Similarly, the expressions "hard coating layer" and "other layers" described later may contain inevitable impurities as long as the effects of the cutting tool according to this embodiment are not impaired.

[0038] The above x is 0.40 or more and 0.60 or less, preferably 0.45 or more and 0.55 or less, and more preferably 0.50 or more and 0.55 or less. When the above x is less than 0.40, MoC 1-x Free carbon precipitates at the grain boundaries of the steel, which tends to reduce the strength. If the above x exceeds 0.60, the strength of the grain boundaries tends to decrease. Therefore, if x is outside the range of 0.40 to 0.60, crack propagation cannot be suppressed and the toughness tends to decrease. The present inventors speculate that such a tendency occurs because the balance between the homogeneity and the strain of the crystal is not appropriate.

[0039] The above x is MoC 1-x It is possible to obtain the MoC ratio by obtaining a cross-sectional sample parallel to the normal direction of the surface of the substrate in the layer, and analyzing the crystal grains that appear in the cross-sectional sample using a scanning electron microscope (SEM) or an energy dispersive X-ray spectroscopy (EDX) device attached to a TEM. 1-x The value of x is calculated by measuring three arbitrary points in the layer, and the average of the three values ​​is taken as the MoC value of the cross-sectional sample. 1-x Here, the "any three points" are the MoC 1-x Three arbitrary 30 nm×30 nm regions are selected in the layer. The EDX device is, for example, a silicon drift detector, JED-2200 (trademark), manufactured by JEOL Ltd. The measurement conditions are as follows.

[0040] EDX measurement conditions Accelerating voltage: 200 kV Probe current: 0.29nA Probe size: 0.2nm

[0041] Furthermore, as long as measurements are performed on the same sample, there is almost no variation in the measurement results even if the measurement area is selected in different locations and performed multiple times, and it has been confirmed that setting the measurement area arbitrarily is not arbitrary.

[0042] The above MoC 1-x The compound represented by the formula (I) has a hexagonal crystal structure. 1-x The compound represented by the formula (I) has a hexagonal crystal structure, 1-x This means that the percentage of the hexagonal crystal structure in the compound represented by the formula (I) is 100 mass %, and does not contain any other crystal structure. 1-x The compound represented by the formula (I) has a hexagonal crystal structure, as described above, for example, in 1-x This can be confirmed by performing X-ray diffraction measurement (XRD measurement) on three arbitrary points in the layer. 1-x When the compound represented by the formula (I) has a hexagonal crystal structure, in the XRD measurement, peaks derived from hexagonal crystal planes such as (100), (002), (101), (102), (110), (103), (112), and (201) are observed at all three measurement points, and peaks derived from crystal planes of crystal systems other than hexagonal are not observed. Examples of the apparatus used for the X-ray diffraction measurement include "SmartLab" (trade name) manufactured by Rigaku Corporation and "X'pert" (trade name) manufactured by PANalytical Corporation. The measurement conditions are as follows.

[0043] XRD measurement conditions Scan axis: 2θ-θ X-ray source: Cu-Kα ray (1.541862Å) Detector: 0-dimensional detector (scintillation counter) Tube voltage: 45kV Tube current: 40mA Incident optics: Use of mirrors Receiving optical system: Use of analyzer crystal (PW3098 / 27) Step: 0.03° Accumulation time: 2 seconds Scan range (2θ): 10°~120°

[0044] As long as measurements are performed on the same sample, there is almost no variation in the measurement results even if the measurement points are changed and measurements are performed multiple times, and it has been confirmed that setting measurement points arbitrarily is not arbitrary.

[0045] <TaC 1-y Layer> In this embodiment, TaC 1-y The layer is TaC 1-y It consists of the compound represented by the formula: "TaC 1-y (hereinafter, "TaC 1-y " refers to tantalum carbide in which the atomic ratio of carbon (C) is 1-y when the atomic ratio of tantalum (Ta) is 1. 1-y The layer may contain unavoidable impurities within a range that does not impair the effects of the cutting tool according to the present embodiment. Examples of the unavoidable impurities include hydrogen, oxygen, nitrogen, and argon. The content ratio of the unavoidable impurities is TaC 1-y It is preferably from 0% by mass to 0.2% by mass relative to the total mass of the layer.

[0046] The above y is 0.40 or more and 0.60 or less, preferably 0.45 or more and 0.55 or less, and more preferably 0.50 or more and 0.55 or less. When the above y is less than 0.40, TaC 1-y Free carbon tends to precipitate at the grain boundaries of the steel, decreasing the strength. Furthermore, when the above y exceeds 0.6, the strength of the grain boundaries tends to decrease. Therefore, when y is outside the above range, crack propagation cannot be suppressed and the toughness tends to decrease. The present inventors speculate that such a tendency occurs because the balance between the homogeneity and strain of the crystal is not appropriate.

[0047] The above y is the above MoC 1-x Similarly, the method for measuring x in a layer can be performed using SEM or TEMThe specific measurement method and conditions are as described above in MoC 1-x The measurement method and conditions for x in the layer shall be the same as those for

[0048] Furthermore, as long as measurements are performed on the same sample, there is almost no variation in the measurement results even if the measurement area is selected in different locations and performed multiple times, and it has been confirmed that setting the measurement area arbitrarily is not arbitrary.

[0049] The above TaC 1-y The compound represented by the formula (I) contains 95% or more by mass of a hexagonal crystal structure. 1-y The content of the hexagonal crystal structure in the compound represented by the formula (I) is preferably 96% by mass or more, more preferably 98% by mass or more, and even more preferably 100% by mass. 1-y It can be confirmed by the following method that the compound represented by the formula (I) contains 95% by mass or more of a hexagonal crystal structure. 1-y XRD measurement was performed on any one point of the layer, and the hexagonal crystal planes (representatively the (100) plane, (002) plane, (101) plane, (110) plane, and (102) plane 、( When n peaks originating from the (103) plane, (112) plane, (201) plane, etc. are confirmed, the peak intensity Ii (i = 1, 2, . . . , n) and half-width Wi (i = 1, 2, . . . , n) are calculated for each peak, and their peak areas ΣSi (Ii × Wi) (i = 1, 2, . . . , n) are calculated. 1-y This is defined as the amount (mass %) of hexagonal crystal structure in the compound represented by the formula:

[0050] When a peak derived from a cubic crystal face (typically the (100), (111), (200), (220), (311), etc.) is observed at the same measurement point as above, the peak area ΣS'i (I'i × W'i) (i = 1, 2, ..., n) is calculated in the same manner as above. The peak area ΣS'i is calculated by TaC 1-y This is defined as the amount (mass %) of cubic crystal structure in the compound represented by the formula:

[0051] The percentage of the hexagonal crystal structure amount ΣSi to the total of the hexagonal crystal structure amount ΣSi and the cubic crystal structure amount ΣS'i (ΣSi / (ΣSi+ΣS'i)×100) is calculated. 1-y The measurement is performed on any three points on the layer, and the average value of (ΣSi / (ΣSi+ΣS'i)×100) of the three points is calculated. The average value is TaC 1-y It is defined as the content (mass%) of the hexagonal crystal structure in the compound represented by the formula:

[0052] In addition, the above TaC 1-y When the compound represented by the formula (100), (002), (101), (110), and (102) are composed of only a hexagonal crystal structure, the (100), (002), (101), (110), and (102) planes are observed at all three measurement points in the XRD measurement. 、( Peaks derived from hexagonal crystal planes such as (103), (112), and (201) planes are observed, and peaks derived from crystal planes of crystal systems other than hexagonal are not observed. 1-x The method for confirming the crystal structure of the compound represented by the formula (I) shall be the same as that used for the compound represented by the formula (I).

[0053] As long as measurements are performed on the same sample, there is almost no variation in the measurement results even if the measurement points are changed and measurements are performed multiple times, and it has been confirmed that setting measurement points arbitrarily is not arbitrary.

[0054] Fig. 2 is a schematic cross-sectional view of a cutting tool according to one aspect of this embodiment. As shown in Fig. 2, the first layer 12 is preferably in contact with the base material 11. In other words, the first layer 12 is preferably provided directly on the base material 11.

[0055] In the cemented carbide of this embodiment, it is preferable that the first layer does not contain free carbon. Here, "the first layer does not contain free carbon" means that the first layer does not contain any free carbon and that the amount of free carbon in the first layer is less than the detection limit. "Free carbon" means carbon that exists as a simple substance without being a constituent element of the first layer. Examples of free carbon include simple substances of carbon that contain carbon-carbon double bonds, such as graphite and soot. The presence or absence of free carbon is confirmed by examining the presence or absence of carbon-carbon double bonds (the presence or absence of C=C peaks in XPS C1s) at any three points on the surface of the first layer using X-ray photoelectron spectroscopy (XPS method). If carbon-carbon double bonds are present at one or more of the above three points, the first layer is determined to contain free carbon. If carbon-carbon double bonds are not present at all of the above three points, the first layer is determined to not contain free carbon. Here, when the first layer is provided on the outermost surface of a coating, the natural oxide layer is oxidized with Ar + The presence or absence of the free carbon is measured after removing it by sputtering or the like. If the first layer is not the outermost surface, Ar + The first layer is exposed by sputtering or the like, and then the presence or absence of the free carbon is measured. An example of an apparatus used for the XPS method is Versa Probe III (product name) manufactured by ULVAC-PHI, Inc. The measurement conditions are as follows.

[0056] XPS measurement conditions X-ray source used: mono-AlKα ray (hν=1486.6eV) Detection depth: 1nm~10nm X-ray beam diameter: approx. 100 μmφ Neutralization gun: Dual type used Ar + :Accelerating voltage 4kV Raster size: 1×1mm Sputtering rate (Ar + ):SiO 2 Sputter conversion value: 28.3nm / min

[0057] As long as measurements are performed on the same sample, there is almost no variation in the measurement results even if the measurement points are changed and measurements are performed multiple times, and it has been confirmed that setting measurement points arbitrarily is not arbitrary.

[0058] The hardness of the first layer is 2700mgf / μm 2 More than 4200mgf / μm 2 It is preferable that the value is less than 2700 mgf / μm 2 More than 4100mgf / μm 2 More preferably, it is 2800 mgf / μm or less. 2 More than 4000mgf / μm 2 It is more preferable that the film hardness is equal to or less than 100 mm. The film hardness is measured by a nanoindenter. Specifically, the film hardness is first obtained by measuring 10 arbitrary points on the surface of the first layer. The average film hardness of the 10 points obtained is then regarded as the film hardness of the first layer of the cross-sectional sample. Here, if the first layer is not the outermost surface, the first layer is exposed by mechanical polishing or the like, and then the measurement is performed by a nanoindenter. An example of the nanoindenter is ENT1100 (product name) manufactured by Elionix Co., Ltd. The measurement conditions are as follows.

[0059] Nanoindenter measurement conditions Indenter: Berkovich Load: 1gf Load time: 10sec Hold time: 2sec Unloading time: 10sec

[0060] As long as measurements are performed on the same sample, there is almost no variation in the measurement results even if the measurement points are changed and measurements are performed multiple times, and it has been confirmed that setting measurement points arbitrarily is not arbitrary.

[0061] The thickness of the first layer is preferably 0.1 μm or more and 10.0 μm or less, more preferably 0.1 μm or more and 7 μm or less, and more preferably 0.5 μm or more and 3 μm or less.

[0062] <Hard coating layer> The coating preferably further includes a hard coating layer disposed between the substrate and the first layer. The hard coating layer preferably includes a first unit layer. The composition of the first unit layer is preferably different from the composition of the first layer. Here, "disposed between the substrate and the first layer" means that the hard coating layer is disposed between the substrate and the first layer, and does not necessarily have to be in contact with the substrate and the first layer. Another layer may be disposed between the substrate and the hard coating layer, or another layer may be disposed between the hard coating layer and the first layer.

[0063] <First unit layer> The first unit layer is preferably made of at least one element selected from the group consisting of Group 4, Group 5, and Group 6 elements, aluminum, and silicon, or made of a compound consisting of at least one element selected from the group consisting of Group 4, Group 5, and Group 6 elements, aluminum, and silicon, and at least one element selected from the group consisting of carbon, nitrogen, oxygen, and boron. The first unit layer is more preferably made of at least one element selected from the group consisting of chromium, aluminum, titanium, and silicon, or made of a compound consisting of at least one element selected from the group consisting of chromium, aluminum, titanium, and silicon, and at least one element selected from the group consisting of carbon, nitrogen, oxygen, and boron. Examples of Group 4 elements include titanium (Ti), zirconium (Zr), and hafnium (Hf). Examples of Group 5 elements include vanadium (V), niobium (Nb), and tantalum (Ta). Examples of group 6 elements of the periodic table include chromium (Cr), molybdenum (Mo), and tungsten (W).

[0064] Examples of the compound contained in the first unit layer include TiAlN, TiAlSiCN, TiAlSiON, TiAlBCN, TiAlSiN, TiCrSiN, TiAlCrSiN, AlCrN, AlCrO, AlCrSiN, TiZrN, TiAlMoN, TiAlNbN, TiSiN, AlCrTaN, AlTiVN, and TiB 2, TiCrHfN, CrSiWN, TiAlCN, TiSiCN, AlZrON, AlCrCN, AlHfN, CrSiBON, CrAlBN, TiAlWN, AlCrMoCN, TiAlBN, TiAlCrSiBCNO, ZrN, ZrB 2 , ZrCN, CrSiBN, AlCrBN, AlCrBON, etc.

[0065] When the hard coating layer consists only of the first unit layer (for example, in the case of FIG. 3), the thickness of the first unit layer (i.e., the hard coating layer) is preferably 0.1 μm or more and 15 μm or less, more preferably 0.1 μm or more and 10 μm or less, and even more preferably 0.5 μm or more and 7 μm or less.

[0066] <Second unit layer> The hard coating layer preferably further includes a second unit layer. The composition of the second unit layer is preferably different from the composition of the first layer and the composition of the first unit layer. The second unit layer is preferably made of at least one element selected from the group consisting of Group 4 elements, Group 5 elements, Group 6 elements, aluminum, and silicon of the periodic table, or made of a compound consisting of at least one element selected from the group consisting of Group 4 elements, Group 5 elements, Group 6 elements, aluminum, and silicon and at least one element selected from the group consisting of carbon, nitrogen, oxygen, and boron. The second unit layer is more preferably made of at least one element selected from the group consisting of chromium, aluminum, titanium, and silicon, or made of a compound consisting of at least one element selected from the group consisting of chromium, aluminum, titanium, and silicon and at least one element selected from the group consisting of carbon, nitrogen, oxygen, and boron. Specific examples of Group 4 elements, Group 5 elements, and Group 6 elements of the periodic table include the above-mentioned elements.

[0067] Examples of the compound contained in the second unit layer include the compounds exemplified above as the compound contained in the first unit layer.

[0068] It is preferable that the first unit layer and the second unit layer are alternately laminated one or more times to form a multilayer structure. That is, as shown in FIG. 4, it is preferable that the hard coating layer 13 includes a multilayer structure consisting of a first unit layer 131 and a second unit layer 132. Here, the multilayer structure may start lamination from either the first unit layer or the second unit layer. That is, the interface on the first layer side in the multilayer structure may be composed of either the first unit layer or the second unit layer. Also, the interface on the opposite side to the first layer side in the multilayer structure may be composed of either the first unit layer or the second unit layer.

[0069] When the hard coating layer has a multi-layer structure, the thickness of the hard coating layer is preferably 0.1 μm to 10 μm, more preferably 0.5 μm to 7 μm. When the hard coating layer has a multi-layer structure, the thickness of the first layer is preferably 0.1 μm to 10 μm, and the thickness of the hard coating layer is preferably 0.1 μm to 10 μm. This improves the chipping resistance and wear resistance of the cutting tool.

[0070] When the hard coating layer includes a multilayer structure, the thickness of the first unit layer is preferably 1 nm or more and 100 nm or less, preferably 1 nm or more and 50 nm or less, and more preferably 2 nm or more and 25 nm or less. Furthermore, the thickness of the second unit layer is preferably 1 nm or more and 100 nm or less, preferably 1 nm or more and 60 nm or less, and more preferably 2 nm or more and 25 nm or less. In one aspect of this embodiment, when the hard coating layer includes a multilayer structure, the thickness of the first unit layer is preferably 1 nm or more and 100 nm or less, and the thickness of the second unit layer is preferably 1 nm or more and 100 nm or less. Here, the "thickness of the first unit layer" means the thickness per layer of the first unit layer. The "thickness of the second unit layer" means the thickness per layer of the second unit layer.

[0071] The number of layers in the multilayer structure may include an embodiment in which one first unit layer and one second unit layer are laminated, as long as the total thickness of the hard coating layer is within the above range, and preferably, 20 to 2500 layers of each of the first and second unit layers are laminated.

[0072] <Other layers> The coating may further include other layers in addition to the first layer and the hard coating layer, provided that the effect of this embodiment is not impaired. The other layers may have compositions different from or the same as those of the first layer and the hard coating layer. The position of the other layers in the coating is not particularly limited. For example, the other layers may include a base layer provided between the substrate and the first layer, an intermediate layer provided between the first layer and the hard coating layer, a surface layer provided on the first layer, and the like. Examples of the other layers include a TiN layer, a TiWCN layer, a TiCN layer, a ZrB 2 layer, TiSiN layer , AlCrN layer, etc.

[0073] The thickness of the other layers is not particularly limited as long as it does not impair the effects of this embodiment. For example, the thickness may be 0.002 μm or more and 10 μm or less. The thickness of the other layers may be 0.003 μm or more and 1 μm or less, 0.003 μm or more and 0.01 μm or less, 0.5 μm or more and 10 μm or less, or 0.5 μm or more and 5 μm or less.

[0074] [Embodiment 2: Manufacturing method of cutting tool] The method for manufacturing a cutting tool according to this embodiment includes a substrate preparing step and a first layer coating step. Each step will be described below.

[0075] <Base material preparation process> In the substrate preparation step, the substrate is prepared. As described above, any substrate that is conventionally known as a substrate of this type can be used. For example, when the substrate is made of cemented carbide, raw powder having a predetermined composition (mass%) is first mixed uniformly using a commercially available attritor. Then, the mixed powder is pressurized into a predetermined shape (for example, SEET13T3AGSN, CNMG120408N-EG, etc.). After that, the pressurized mixed powder is sintered in a predetermined sintering furnace at 1300 to 1500°C or less for 1 to 2 hours to obtain the substrate made of cemented carbide. In addition, a commercially available product may be used as it is as the substrate. An example of a commercially available product is EH520 (trademark) manufactured by Sumitomo Electric Hardmetal Corporation.

[0076] <First layer coating process> In the first layer coating step, at least a part of the surface of the substrate is coated with the first layer to obtain a cutting tool. Here, "at least a part of the surface of the substrate" includes a part that contacts the workpiece during cutting. The part that contacts the workpiece can be, for example, a region of the substrate surface that is within 2 mm of the cutting edge.

[0077] The method for covering at least a part of the substrate with the first layer is not particularly limited, and may be, for example, a method for forming the first layer by physical vapor deposition (PVD).

[0078] As the physical vapor deposition method, any conventionally known physical vapor deposition method can be used without any particular limitation. Examples of such physical vapor deposition methods include sputtering, ion plating, arc ion plating, and electron ion beam deposition. In particular, the use of cathodic arc ion plating or sputtering, which has a high ionization rate of the raw material element, is preferable because it allows metal bombardment and / or gas ion bombardment treatment to be performed on the substrate surface before forming the coating, thereby significantly improving the adhesion between the coating and the substrate.

[0079] <MoC 1-xLayer formation≫ Mo has a high melting point and is difficult to melt. Therefore, it is not possible to maintain a stable discharge in the physical vapor deposition method, and it is not possible to form a MoC layer made of hexagonal MoC and having good film quality. 1-x MoC with good film quality 1-x As an example of such a method, we have discovered a method for stably producing MoC layers with a hexagonal crystal structure by the arc ion plating method. 1-x The case of forming a layer (0.40≦x≦0.60) will be described below.

[0080] First, a MoC target is set in the arc type evaporation source in the device, the substrate (base material) temperature is set to 450 to 600°C, and evacuation is performed. Next, for example, argon gas and / or krypton gas are introduced, and the gas pressure in the device is set to 1.0 to 3.0 Pa. Then, a negative bias voltage of 200 to 1000 V is applied to the substrate via a DC power source to clean the surface of the base material for 40 minutes. After that, an arc current of 80 to 200 A is supplied to the cathode electrode, and metal ions and the like are generated from the arc type evaporation source to form hexagonal MoC. 1-x A layer (0.40≦x≦0.60) can be formed. At this time, MoC 1-x In the initial stage of layer formation (when the film thickness is in the range of 0.1 μm or less), the substrate temperature is set to 400 to 450° C. and the substrate bias is set to −50 V, and toward the end of formation, the temperature is gradually increased to 450 to 550° C. and the substrate bias to −60 to −75 V. An example of an apparatus used in the arc ion plating method is AIP (product name) manufactured by Kobe Steel, Ltd.

[0081] <<TaC 1-y Layer formation≫ Ta has a high melting point and is difficult to melt. Therefore, it is not possible to maintain a stable discharge in the physical vapor deposition method, and it is not possible to form a TaC layer containing cubic TaC and having good film quality. As a result of extensive research, the inventors of the present invention have found that hexagonal TaC 1-y TaC with good film quality including 1-yAs an example of such a method, we have found a method for stably producing a TaC layer containing 95% or more of a hexagonal crystal structure by the arc ion plating method. 1-y The case of forming a layer (0.40≦y≦0.60) will be described below.

[0082] First, a TaC target is set in the arc type evaporation source in the device, the substrate (base material) temperature is set to 450 to 600°C, and evacuation is performed. Next, for example, argon gas and / or krypton gas are introduced, and the gas pressure in the device is set to 1.0 to 3.0 Pa. Then, a negative bias voltage of 200 to 1000 V is applied to the substrate via a DC power source to clean the surface of the base material for 40 minutes. Thereafter, an arc current of 80 to 200 A is supplied to the cathode electrode, and metal ions and the like are generated from the arc type evaporation source to form TaC containing 95 mass % or more of a hexagonal crystal structure. 1-y A layer (0.40≦y≦0.60) can be formed. At this time, TaC 1-y In the early stage of the layer formation (when the film thickness is in the range of 0.1 μm or less), the substrate temperature is set to 400 to 450° C. and the substrate bias is set to −50 V, and toward the end of the formation, the temperature is gradually increased to 450 to 550° C. and the substrate bias to −60 to −75 V. An example of an apparatus used in the arc ion plating method is AIP (product name) manufactured by Kobe Steel, Ltd.

[0083] <Hard coating layer coating process> The manufacturing method of the cutting tool according to the present embodiment preferably further includes a hard coating layer coating step prior to the first layer coating step. The method for forming the hard coating layer is not particularly limited, and a conventional method can be used. Specifically, for example, the hard coating layer can be formed by the above-mentioned PVD method.

[0084] <Other processes> In addition to the above-mentioned steps, the manufacturing method according to the present embodiment may include a base layer coating step of forming a base layer between the substrate and the first layer, an intermediate layer coating step of forming an intermediate layer between the first layer and the hard coating layer, and a surface layer coating step of forming a surface layer on the first layer. When forming other layers such as the above-mentioned base layer, intermediate layer, and surface layer, the other layers may be formed by a conventional method. Specifically, for example, the other layers may be formed by the above-mentioned PVD method.

[0085] Furthermore, the manufacturing method according to the present embodiment may include a metal bombardment process, a peening process, and a process of performing a surface treatment, as appropriate. For example, the metal bombardment process may include a method of evaporating Ti cathode in an argon gas atmosphere, mixing the substrate surface, and forming a mixing layer. For example, the surface treatment may include polishing with abrasive grains and brush polishing. More specifically, a method using a media in which diamond powder is supported on an elastic material may be used. For example, the Sirius Z manufactured by Fuji Manufacturing Co., Ltd. may be used as an apparatus for performing the above surface treatment.

[0086] [Appendix 1] A cutting tool according to the present disclosure includes a substrate and a coating disposed on the substrate, The coating is MoC 1-x MoC consisting of the compound represented by 1-x layer, The x is equal to or greater than 0.40 and equal to or less than 0.60, Said MoC 1-x The compound represented by the formula (I) is a cutting tool having a hexagonal crystal structure.

[0087] [Appendix 2] Said MoC 1-x The layer preferably does not contain free carbon.

[0088] [Appendix 3] Said MoC 1-x The hardness of the layer is 2700mgf / μm 2 More than 4200mgf / μm 2It is preferable that:

[0089] [Appendix 4] Said MoC 1-x The layer is preferably in contact with the substrate.

[0090] [Appendix 5] A cutting tool according to the present disclosure includes a substrate and a coating disposed on the substrate, The coating is TaC 1-y TaC consisting of the compound represented by 1-y layer, The y is equal to or greater than 0.40 and equal to or less than 0.60, The TaC 1-y The compound represented by the formula (I) is a cutting tool containing 95 mass % or more of a hexagonal crystal structure.

[0091] [Appendix 6] The TaC 1-y The layer preferably does not contain free carbon.

[0092] [Appendix 7] The TaC 1-y The hardness of the layer is 2700mgf / μm 2 More than 4200mgf / μm 2 It is preferable that:

[0093] [Appendix 8] The TaC 1-y The layer is preferably in contact with the substrate. EXAMPLES

[0094] The present embodiment will be described in more detail with reference to examples, although the present embodiment is not limited to these examples.

[0095] Example 1 <Cutting tool manufacturing> [Sample 1 to Sample 26] <Base material preparation process> As a substrate, JIS standard K10 super hard (shape: JIS standard SEET13T3AGSN-L, CNMG120408N-EG) was prepared. Next, the substrate was set at a predetermined position in an arc ion plating device (manufactured by Kobe Steel, Ltd., product name: AIP).

[0096] <First layer (MoC 1-x Layer) Coating process> MoC is deposited on the above substrate by arc ion plating. 1-x A MoC layer was formed. Specifically, the method is as follows. First, an MoC target is set in the arc type evaporation source in the device, the substrate (base material) temperature is set to 450 to 600°C, and evacuation is performed. Next, for example, one or both of argon gas and krypton gas are introduced, and the gas pressure in the device is set to 1.0 to 3.0 Pa. Then, a negative bias voltage of 200 to 1000 V is applied to the substrate via a DC power source to clean the surface of the base material for 40 minutes. After that, an arc current of 80 to 200 A is supplied to the cathode electrode, and metal ions and the like are generated from the arc type evaporation source, thereby forming a MoC 1-x A layer (0.40≦x≦0.60) is formed. At this time, MoC 1-x In the initial stage of the formation of the layer (when the film thickness is in the range of 0.1 μm or less), the substrate temperature is set to 400 to 450° C. and the substrate bias is set to −50 V. Toward the end of the formation, the temperature is gradually increased to 450° C. to 550° C. and the substrate bias is increased to −60 to −75 V. 1-x MoC up to the thickness specified in the "Thickness" column of "Layer" 1-x The arc ion plating method was performed using an apparatus called AIP (product name) manufactured by Kobe Steel, Ltd.

[0097] <Undercoat layer coating process> Substrate and MoC 1-x For the samples with an underlayer between the MoC layer and the MoC film (samples 5 and 6), 1-xBefore performing the layer coating process, an underlayer was formed on the substrate by the following procedure. First, a target containing the metal composition in the column of the underlayer composition in Table 1 was set in the arc type evaporation source of the arc ion plating device. Next, the substrate temperature was set to 600°C and the gas pressure in the device was set to 1 Pa. In the case of the nitride underlayer (sample 5), a mixed gas of nitrogen gas and argon gas was introduced. In the case of the carbonitride underlayer (sample 6), a mixed gas of nitrogen gas, methane gas, and argon gas was introduced as the reactive gas. Then, an arc current of 150A was supplied to the cathode electrode. By supplying the arc current, metal ions and the like were generated from the arc type evaporation source, and the underlayer was formed to the thickness listed in parentheses in the "underlayer" in Table 1.

[0098] <Hard coating layer coating process> Substrate and MoC 1-x For the samples with a hard coating layer between the MoC layer (samples 7 to 13, 16 to 22, 25, and 26), 1-x Before performing the layer coating process, a hard coating layer was formed on the substrate by the following procedure. First, a target containing the metal composition in the column of the composition of the hard coating layer described in Tables 1 and 2 was set in the arc type evaporation source of the arc ion plating device. Next, the substrate temperature was set to 550°C and the gas pressure in the device was set to 4.0 Pa. As the reactive gas, nitrogen gas was introduced in the case of a nitride hard coating layer. In the case of a carbonitride hard coating layer, a mixed gas of nitrogen gas and methane gas was introduced as the reactive gas. In the case of an oxynitride hard coating layer, a mixed gas of oxygen gas and nitrogen gas was introduced as the reactive gas. Then, an arc current of 150A was supplied to the cathode electrode. By generating metal ions and the like from the arc type evaporation source by supplying the arc current, a hard coating layer was formed to the thickness described in parentheses in the "hard coating layer" in Tables 1 and 2.

[0099] When forming a multilayered hard coating layer, the multilayered structure was formed by repeatedly stacking the first unit layer and the second unit layer until the desired thickness was reached, starting from the left side in Tables 1 and 2. For example, in sample 11, a first unit layer having a thickness of 5 nm and made of TiAlBN and a second unit layer having a thickness of 5 nm and made of TiSiN were alternately stacked to form a multilayered structure having a thickness of 1.0 μm.

[0100] <Surface layer coating process> MoC 1-x For the samples with a surface layer on the MoC layer (samples 5, 7, 8, 11, and 12), 1-x After the layer coating process, the MoC 1-x A surface layer was formed on the layer. First, a target containing the metal composition in the column of the composition of the surface layer in Table 1 was set in the arc type evaporation source of the arc ion plating device. Next, the substrate temperature was set to 550°C and the gas pressure in the device was set to 4.0 Pa. In the case of a nitride surface layer, a mixed gas of nitrogen gas and argon gas was introduced as a reactive gas. Then, an arc current of 150 A was supplied to the cathode electrode. By supplying an arc current, metal ions and the like were generated from the arc type evaporation source, and a surface layer was formed to the thickness listed in parentheses in the "surface layer" in Table 1.

[0101] [Sample 1-1] The same substrate as Sample 1 was prepared as the substrate. MoC 1-x A MoC layer was formed. Specifically, the method was as follows. First, the MoC target was set in the arc type evaporation source of the arc ion plating device. Next, the substrate temperature was set to 390°C and the gas pressure inside the device was set to 2 Pa. Argon gas was introduced as the gas. Then, while the substrate bias voltage was maintained at -50 V, an arc current of 120 A was supplied to the cathode electrode. Metal ions and the like were generated from the arc type evaporation source by supplying the arc current, and the MoC 1-x The layers were formed to obtain a cutting tool.

[0102] [Sample 1-2] The same substrate as Sample 1 was prepared as the substrate. MoC 1-x A MoC layer was formed. Specifically, the method was as follows. First, the MoC target was set in the arc type evaporation source of the arc ion plating device. Next, the substrate temperature was set to 620°C and the gas pressure inside the device was set to 0.5 Pa. Argon gas was introduced as the gas. Then, while the substrate bias voltage was maintained at -40 V, an arc current of 130 A was supplied to the cathode electrode. Metal ions and the like were generated from the arc type evaporation source by supplying the arc current, and the MoC 1-x The layers were formed to obtain a cutting tool.

[0103] [Sample 1-3] The same substrate as Sample 1 was prepared as the substrate. WC was deposited on the substrate by the method described in Patent Document 1. 0.56 The layers were formed to obtain a cutting tool.

[0104] [Sample 1-4] The same substrate as that of Sample 1 was prepared. A TiN layer (underlayer) and an AlTiN layer were formed on the substrate in the above order. The TiN layer was formed in the same manner as that of Sample 5. The AlTiN layer was formed in the same manner as that of the first unit layer of Sample 12.

[0105] <Evaluation of cutting tool characteristics> The MoC of each sample prepared as described above 1-x The composition x, the crystal structure and the content of the crystal structure, the presence or absence of free carbon, and the hardness of the layer were measured. Regarding hardness, the hardness of the hard coating layer was measured for Samples 1-3 and 1-4. The specific measurement method is described in the first embodiment, so the description will not be repeated. The results are shown in the "MoC 1-x "composition x", "crystal structure", "content (mass%)", "free carbon" and "hardness (mgf / μm)" of "layer" 2 In Tables 1 and 2, the notation "None" in the "Free carbon" column indicates that 1-x It means that there is no free carbon in the layer, and "Yes" means that there is no free carbon in the layer. 1-xThis indicates that the layer contains free carbon. Sample 1 - Sample 2 6 In the samples 1-1 and 1-2, MoC 1-x It was confirmed that the layer was composed of 100% by mass of a hexagonal crystal structure.

[0106] MoC 1-x The thicknesses of the layer, underlayer, hard coating layer (first unit layer, second unit layer) and coating were measured. The specific measurement method is described in the first embodiment, so the description will not be repeated. The results are shown in Tables 1 and 2. In Tables 1 and 2, the notation "-" in "underlayer" and "hard coating layer" indicates that the corresponding layer is not present in the coating. Also, the notation "TiAlBN (5 nm) / TiSiN (5 nm) multilayer structure (1.0 μm)" in "hard coating layer" indicates that the hard coating layer is formed of a multilayer structure (total thickness 1.0 μm) in which a TiAlBN layer (first unit layer) having a thickness of 5 nm and a TiSiN layer (second unit layer) having a thickness of 5 nm are alternately laminated.

[0107] [Table 1]

[0108] [Table 2]

[0109] <Cutting test 1> Using each sample cutting tool prepared as described above, the cutting time until the cutting tool was chipped was measured under the following cutting conditions, and the chipping resistance of the cutting tool was evaluated. The following cutting conditions correspond to high-load, high-speed, high-efficiency machining. The results are shown in Tables 1 and 2. The longer the cutting time, the better the chipping resistance.

[0110] (Cutting conditions for fracture resistance test (face milling test)) Insert: SEET13T3AGSN-L Work material (material): Ti-6Al-4V Speed:70m / min Feed: 0.1mm / tooth Cutting: Depth: 5mm, Radial Cutting: 10mm

[0111] <Cutting test 2> Using each sample cutting tool prepared as described above, cutting tests were performed under the following cutting conditions to evaluate the wear resistance of the cutting tools. The following cutting conditions correspond to high-load, high-speed, high-efficiency machining. The results are shown in Tables 1 and 2. The longer the cutting time, the better the wear resistance.

[0112] (Cutting conditions for wear resistance test (external diameter turning test)) Insert: CNMG120408N-EG Work material (material): Ti-6Al-4V Speed: 140m / min Feed: 0.15mm / tooth Cutting depth: 0.8mm Life criterion: Time when flank wear exceeds 0.2 mm

[0113] From the results of the cutting tests, it was confirmed that the cutting tools of Samples 1 to 26 corresponding to the examples have superior chipping resistance and wear resistance even in high-speed, high-efficiency machining with a high load, and have a longer tool life, compared to the cutting tools of Samples 1-1 to 1-4 corresponding to the comparative examples. 6 It was suggested that the cutting tool is suitable for high-speed, high-efficiency machining applications with high loads, especially applications where chipping resistance and wear resistance are required.

[0114] Example 2 <Cutting tool manufacturing> [Sample 1A to Sample 25A] <Base material preparation process> As a substrate, JIS standard K10 cemented carbide (shape: JIS standard SEET13T3AGSN-L, CNMG120408N-EG) was prepared. Next, the substrate was set at a predetermined position in an arc ion plating device (manufactured by Kobe Steel, Ltd., product name: AIP).

[0115] <First layer (TaC 1-y Layer) Coating process> TaC is deposited on the above substrate by arc ion plating. 1-y A TaC layer was formed. Specifically, the method was as follows. First, a TaC target was set in an arc-type evaporation source in the device, the substrate (base material) temperature was set to 450 to 600°C, and evacuation was performed. Next, for example, one or both of argon gas and krypton gas were introduced, and the gas pressure in the device was set to 1.0 to 3.0 Pa. Then, a negative bias voltage of 200 to 1000 V was applied to the substrate via a DC power source to clean the surface of the base material for 40 minutes. After that, an arc current of 80 to 200 A was supplied to the cathode electrode, and metal ions and the like were generated from the arc-type evaporation source to form a TaC layer containing 95 mass % or more of a hexagonal crystal structure. 1-y A layer (0.40≦y≦0.60) is formed. At this time, TaC 1-y In the initial stage of the formation of the layer (when the film thickness is in the range of 0.1 μm or less), the substrate temperature is set to 400 to 450° C. and the substrate bias is set to −50 V. Toward the end of the formation, the temperature is gradually increased to 450° C. to 550° C. and the substrate bias is increased to −60 to −75 V. 1-y Layer" to the thickness specified in the "Thickness" column. 1-y The arc ion plating method was performed using an apparatus called AIP (product name) manufactured by Kobe Steel, Ltd.

[0116] <Undercoat layer coating process> Substrate and TaC 1-y For the samples with an underlayer between the TaC layer and the TaC layer (samples 5A and 6A), 1-yBefore performing the layer coating process, an underlayer was formed on the substrate by the following procedure. First, a target containing a metal composition in the column of the underlayer composition in Table 3 was set in the arc type evaporation source of an arc ion plating device. Next, the substrate temperature was set to 600°C and the gas pressure in the device was set to 1 Pa. In the case of the nitride underlayer (sample 5A), a mixed gas of nitrogen gas and argon gas was introduced. In the case of the carbonitride underlayer (sample 6A), a mixed gas of nitrogen gas, methane gas and argon gas was introduced as the reactive gas. Then, an arc current of 150 A was supplied to the cathode electrode. By generating metal ions and the like from the arc type evaporation source by supplying the arc current, an underlayer was formed to the thickness listed in parentheses in the "underlayer" in Table 3.

[0117] <Hard coating layer coating process> Substrate and TaC 1-y For the samples with a hard coating layer between the TaC layer (samples 7A to 13A, and samples 17A to 25A), 1-y Before performing the layer coating process, a hard coating layer was formed on the substrate by the following procedure. First, a target containing the metal composition in the column of the composition of the hard coating layer described in Tables 3 and 4 was set in the arc type evaporation source of the arc ion plating device. Next, the substrate temperature was set to 550°C and the gas pressure in the device was set to 4.0 Pa. As the reaction gas, a mixed gas of nitrogen gas and argon gas was introduced in the case of a hard coating layer of a nitride. As the reaction gas, a mixed gas of nitrogen gas and methane gas was introduced in the case of a hard coating layer of a carbonitride. As the reaction gas, a mixed gas of oxygen gas and nitrogen gas was introduced in the case of a hard coating layer of an oxynitride. Then, an arc current of 150A was supplied to the cathode electrode. By generating metal ions and the like from the arc type evaporation source by supplying an arc current, a hard coating layer was formed to the thickness described in parentheses in the "hard coating layer" in Tables 3 and 4.

[0118] When forming a multilayered hard coating layer, the multilayered structure was formed by repeatedly stacking the first unit layers and the second unit layers in the order listed on the left side of Tables 3 and 4 until the desired thickness was reached. For example, in sample 11A, a 6 nm-thick first unit layer made of TiAlBN and a 6 nm-thick second unit layer made of TiSiN were alternately stacked to form a 1.0 μm-thick multilayered structure.

[0119] <Surface layer coating process> TaC 1-y For the samples with a surface layer on the TaC 1-y After the TaC layer coating process, 1-y A surface layer was formed on the layer. First, a target containing the metal composition in the column of the composition of the surface layer in Table 3 was set in the arc type evaporation source of the arc ion plating device. Next, the substrate temperature was set to 550°C and the gas pressure in the device was set to 4.0 Pa. In the case of a nitride surface layer, a mixed gas of nitrogen gas and argon gas was introduced as a reactive gas. Then, an arc current of 150 A was supplied to the cathode electrode. By supplying an arc current, metal ions and the like were generated from the arc type evaporation source, and a surface layer was formed to the thickness listed in parentheses in the "surface layer" in Table 3.

[0120] [Sample 1-1A] The same substrate as Sample 1A was prepared as a substrate. On the substrate, TaC was deposited by arc ion plating. 1-y A TaC layer was formed. Specifically, the method was as follows. First, a TaC target was set in the arc type evaporation source of an arc ion plating device. Next, the substrate temperature was set to 380°C and the gas pressure inside the device was set to 1.5 Pa. Argon gas was introduced as the gas. Then, while the substrate bias voltage was maintained at -55 V, an arc current of 120 A was supplied to the cathode electrode. Metal ions and the like were generated from the arc type evaporation source by supplying an arc current, and the TaC 1-y The layers were formed to obtain a cutting tool.

[0121] [Sample 1-2A] The same substrate as Sample 1A was prepared as a substrate. On the substrate, TaC was deposited by arc ion plating. 1-y A TaC layer was formed. Specifically, the method was as follows. First, a TaC target was set in the arc type evaporation source of an arc ion plating device. Next, the substrate temperature was set to 610°C and the gas pressure inside the device was set to 0.8 Pa. Argon gas was introduced as the gas. Then, while the substrate bias voltage was maintained at -43 V, an arc current of 120 A was supplied to the cathode electrode. Metal ions and the like were generated from the arc type evaporation source by supplying an arc current, and the TaC 1-y The layers were formed to obtain a cutting tool.

[0122] [Sample 1-3A] The same substrate as Sample 1A was prepared as the substrate. WC was deposited on the substrate by the method described in Patent Document 1. 0.56 The layers were formed to obtain a cutting tool.

[0123] [Sample 1-4A] The same substrate as Sample 1A was prepared as the substrate. A TiN layer (underlayer) and an AlTiN layer were formed on the substrate in the above order. The TiN layer was the same as Sample 5. A The AlTiN layer was formed in the same manner as the first unit layer of sample 12A.

[0124] [Sample 1-5A] The same substrate as Sample 1 was prepared as a substrate. On the substrate, TaC was deposited by arc ion plating. 1-y A TaC layer was formed. Specifically, the method was as follows. First, a TaC target was set in the arc type evaporation source of an arc ion plating device. Next, the substrate temperature was set to 420°C and the gas pressure inside the device was set to 1 Pa. Argon gas was introduced as the gas. Then, while the substrate bias voltage was maintained at -69 V, an arc current of 120 A was supplied to the cathode electrode. Metal ions and the like were generated from the arc type evaporation source by supplying an arc current, and the TaC 1-y The layers were formed to obtain a cutting tool.

[0125] <Evaluation of cutting tool characteristics> The TaC of each sample prepared as described above 1-y For the layer, composition y, crystal structure, hexagonal TaC 1-y The content of free carbon, the presence or absence of free carbon, and the hardness were measured. The specific measurement method is described in the first embodiment, so the description will not be repeated. The results are shown in Tables 3 and 4 under "TaC 1-y "Composition y" of the layer, "crystal structure", Six Square content (mass%), free carbon, and hardness (mgf / μm 2 The notation "hexagonal + cubic" in the "Crystal Structure" column of Tables 3 and 4 refers to TaC 1-y Hexagonal TaC in the layer 1-y and cubic TaC 1-y For example, in sample 16A, hexagonal TaC 1-y is present at 95% by mass, and the remaining (5% by mass) is cubic TaC 1-y In the "Free carbon" column of Tables 3 and 4, "None" indicates that TaC 1-y This indicates that the layer does not contain free carbon, and "present" indicates that the layer does not contain free carbon. 1-y This indicates that the layer contains free carbon.

[0126] TaC 1-y The thicknesses of the layer, underlayer, hard coating layer (first unit layer, second unit layer) and coating were measured. The specific measurement method is described in the first embodiment, so the description will not be repeated. The results are shown in Tables 3 and 4. In Tables 3 and 4, the notation "-" in "underlayer" and "hard coating layer" indicates that the corresponding layer is not present in the coating. Also, the notation "TiAlBN (6 nm) / TiSiN (6 nm) multilayer structure (1.0 μm)" in "hard coating layer" indicates that the hard coating layer is formed of a multilayer structure (total thickness 1.0 μm) in which a TiAlBN layer (first unit layer) having a thickness of 6 nm and a TiSiN layer (second unit layer) having a thickness of 6 nm are alternately laminated.

[0127] [Table 3]

[0128] [Table 4]

[0129] <Cutting test 1> Using each sample cutting tool prepared as described above, the cutting time until the cutting tool was chipped was measured under the same cutting conditions as in Cutting Test 1 of Example 1, and the chipping resistance of the cutting tool was evaluated. The cutting conditions correspond to high-speed, high-efficiency machining. The results are shown in Tables 3 and 4. A longer cutting time indicates better chipping resistance.

[0130] <Cutting test 2> Using each sample cutting tool prepared as described above, a cutting test was performed under the same cutting conditions as in Cutting Test 2 of Example 1 to evaluate the wear resistance of the cutting tool. The cutting conditions correspond to high-speed, high-efficiency machining. The results are shown in Tables 3 and 4. The longer the cutting time, the better the wear resistance.

[0131] From the results of the cutting tests, it was confirmed that the cutting tools of Samples 1A to 25A corresponding to the examples have superior chipping resistance and wear resistance even in high-speed, high-efficiency machining, and have a long tool life, compared to the cutting tools of Samples 1-1A to 1-5A corresponding to the comparative examples. This suggests that the cutting tools of Samples 1A to 25A corresponding to the examples are suitable for high-speed, high-efficiency machining applications with high loads, particularly applications requiring chipping resistance and wear resistance.

[0132] Although the embodiments and examples of the present invention have been described above, it is also intended from the beginning that the configurations of the above-described embodiments and examples may be appropriately combined.

[0133] The embodiments and examples disclosed herein are illustrative in all respects and should not be considered as limiting. The scope of the present invention is indicated by the claims, not by the embodiments and examples described above, and is intended to include the meaning equivalent to the claims and all modifications within the scope. [Explanation of symbols]

[0134] 1 cutting face, 2 flank face, 3 cutting edge ridge, 4 coating, 10 cutting tool, 11 substrate, 12 first layer, 13 hard coating layer, 131 first unit layer, 132 second unit layer.

Claims

1. 1. A cutting tool comprising a substrate and a coating disposed on the substrate, the coating includes a first layer and a hard coat layer disposed between the substrate and the first layer; The first layer is TaC 1-y TaC consisting of a compound represented by the formula: 1-y It consists of layers, The TaC 1-y The compound represented by the formula (I) contains 95% by mass or more of a hexagonal crystal structure, The y is 0.40 or more and 0.60 or less, The hard coating layer includes a first unit layer, A cutting tool, wherein the first unit layer is made of TiAlBCN, TiAlSiN, TiSiN, TiAlBN, CrSiBN, AlCrBN, or AlCrBON.

2. A cutting tool comprising a substrate and a coating disposed on the substrate, the coating includes a first layer and a hard coat layer disposed between the substrate and the first layer; The first layer is a TaC 1-y layer made of a compound represented by TaC 1-y , The compound represented by TaC 1-y contains 95% by mass or more of a hexagonal crystal structure, The y is 0.40 or more and 0.60 or less, the hard coating layer includes a first unit layer and a second unit layer, The composition of the first unit layer is different from the composition of the second unit layer, the first unit layer is made of TiAlN or AlCrN, the second unit layer is made of TiAlN or AlCrN, A cutting tool, wherein the first unit layer and the second unit layer are each alternately stacked in one or more layers to form a multilayer structure.

3. The cutting tool of claim 1 or 2, wherein the first layer is free of free carbon.

4. The hardness of the first layer is 2700 mgf / μm 2 More than 4200mgf / μm 2 4. A cutting tool according to claim 1, wherein:

5. the hard coating layer is composed of the first unit layer, The cutting tool according to claim 1 , wherein the first unit layer has a thickness of 0.1 μm or more and 15 μm or less.

6. The first unit layer is made of TiAlSiN, TiSiN, TiAlBN, or AlCrBN, The hard coating layer further includes a second unit layer, The composition of the second unit layer is different from the composition of the first unit layer, the second unit layer is made of TiAlSiN, TiSiN, TiAlBN, or AlCrBN; The cutting tool according to claim 1 , wherein the first unit layers and the second unit layers are alternately stacked one or more times to form a multi-layer structure.

7. The thickness of the first unit layer is 1 nm or more and 100 nm or less, The cutting tool according to claim 2 or 6, wherein the second unit layer has a thickness of 1 nm or more and 100 nm or less.

8. The thickness of the first layer is 0.1 μm or more and 10 μm or less, The cutting tool according to claim 1 , wherein the hard coating layer has a thickness of 0.1 μm or more and 10 μm or less.

9. The cutting tool according to claim 1 , wherein the coating has a thickness of 0.2 μm or more and 20 μm or less.

10. 10. The cutting tool according to claim 1, wherein the substrate comprises at least one selected from the group consisting of cemented carbide, cermet, high speed steel, ceramics, a cubic boron nitride sintered body, and a diamond sintered body.

Citation Information

Patent Citations

  • Tacno coatings and production process

    EP3461928A1

  • High strength coated member with crystal orientational property

    JP1997170068A

  • Coated cutting tools

    JP2013516331A

  • Hard film, hard film coated member, and production method of hard film

    JP2018059146A

  • Surface-coated cutting tool

    WO2019181742A1